Root Canal Configuration of Mandibular First and Second Premolars in an Iranian Population - Nemat Eskandarzadeh; Hakimeh Manafi; Hamid Reza Yavari; Shahriar Shahi; Saeed Rahimi (Tabriz University of Medical Sciences, 2007)
Background and aims. It is critical to have a proper knowledge of the normal anatomy of the pulp and its variations for the success of endodontic treatment. The aim of this study was to determine the canal configuration and the prevalence of C-shaped canals in mandibular first and second premolars in a North-Western Iranian population. Materials and methods. A total of 163 extracted mandibular first and 103 mandibular second premolars were injected with India ink and demineralized . They were made clear and transparent with methyl salicylate and the anatomy of their canal(s) was studied. Results. The results showed that 98% of mandibular first premolars had one root, 2% had two roots, 70.6% had one canal, 27.8% had two canals, 1.2% had three canals and the prevalence of C-shaped canals was 2.4%. All mandibular second premolars had one root, 80.5% had one canal, 17.5% had two canals and the prevalence of C-shaped canals was 2%. Conclusion. It is important that clinicians, before treatment of mandibular first and second premolars, pay complete attention to radiographs, have a true concept of the number of root(s) and canal(s), and prepare a correct access cavitiy.